Application of Management Information System to Strengthen Community Livestock Business of Goat and Sheep Farmers - Kusumawati, Enike Dwi; Zaini, Akhmad Zaini; Sarwoko, Endi Sarwoko; Mahmud, Ali Mahmud; Ramayanti, Kinta Ramayanti; Pamungkasih, Estri Pamungkasih; Ristanti, Rahmadina Fitria Ristanti; Arini, Iftita Yustitia Arini; Pradana, Diva Cahyo Pradana; Fachthurrohman, Muchammad Fachthurrohman; Ashari, Farhan Ashari; Pinastico, Stephanus Herin Pinastico; Nugke, Haydar Wafiq (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2024)
Sheep and goat farming is one of the superior livestock products of Malang Regency. This goat and sheep farming business is a livestock business carried out by breeders in 12 villages in Wagir District, Malang Regency as the main supporter of starting a goat and sheep center. Farmers still do not have historical livestock data so it may be difficult to trace livestock history. Therefore, it is necessary to record data using the application of a digital management information system. The method used in this service activity is a participatory action and learning system approach which includes Focus Group Discussion (FGD), training and direct practice, mentoring and field monitoring of the results of the transfer of livestock management information system technology in 12 villages. Community service activities have been running very well and successfully with the support and cooperation of all partners and breeders in Wagir District and Malang Regency. This good cooperation needs to be maintained and further improved. The results of the activity showed a significant increase in awareness, knowledge and skills of sheep and goat breeders in using livestock management information systems to strengthen community livestock business management.